2019
DOI: 10.1021/acs.langmuir.8b03659
|View full text |Cite
|
Sign up to set email alerts
|

Control of Stratification in Drying Particle Suspensions via Temperature Gradients

Abstract: A potential strategy for controlling stratification in a drying suspension of bidisperse particles is studied using molecular dynamics simulations. When the suspension is maintained at a constant temperature during fast drying, it can exhibit "small-on-top" stratification with an accumulation (depletion) of smaller (larger) particles in the top region of the drying film, consistent with the prediction of current theories based on diffusiophoresis. However, when only the region near the substrate is thermalized… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 57 publications
3
30
0
Order By: Relevance
“…One can incorporate the hydrodynamic interactions by including the concentration-dependence in the diffusion constant. There are many recent studies on the effect of hydrodynamics on the non-equilibrium colloidal dynamics, mostly by evaporation [30][31][32][33][34][35] . One study on polymer solutions by Statt et al 32 showed that stratification happens in implicit solvent simulations, but not in explicit solvent simulations when hydrodynamic effects are included.…”
Section: Discussionmentioning
confidence: 99%
“…One can incorporate the hydrodynamic interactions by including the concentration-dependence in the diffusion constant. There are many recent studies on the effect of hydrodynamics on the non-equilibrium colloidal dynamics, mostly by evaporation [30][31][32][33][34][35] . One study on polymer solutions by Statt et al 32 showed that stratification happens in implicit solvent simulations, but not in explicit solvent simulations when hydrodynamic effects are included.…”
Section: Discussionmentioning
confidence: 99%
“…can easily be added to the model as additional energy terms. While the method is described for MC simulations in this study, possible extensions based on the molecular dynamics (MD) method are conceivable [ 30 , 31 , 32 ].…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…Previous studies demonstrated that self-stratification will only happen for polymers of specific chemistry or particle mixtures of certain size ratios when a coating suspension dries. [13][14][15][16][17][18] These constraints severely limit the application of self-stratification in common coating materials. In order to achieve effective stratification, current coating formulation and binder chemistry need to be comprehensively altered, which demands significant efforts.…”
Section: Introductionmentioning
confidence: 99%